Economics for the Common Good - Tirole, Jean; Rendall, Steven (Princeton, NJ : Princeton University Press, 2017)
From Nobel Prize-winning economist Jean Tirole, a bold new agenda for the role of economics in societyWhen Jean Tirole won the 2014 Nobel Prize in Economics, he suddenly found himself being stopped in the street by complete strangers and asked to comment on issues of the day, no matter how distant from his own areas of research. His transformation from academic economist to public intellectual prompted him to reflect further on the role economists and their discipline play in society. The result is Economics for the Common Good, a passionate manifesto for a world in which economics, far from being a "dismal science," is a positive force for the common good.Economists are rewarded for writing technical papers in scholarly journals, not joining in public debates. But Tirole says we urgently need economists to engage with the many challenges facing society, helping to identify our key objectives and the tools needed to meet them.To show how economics can help us realize the common good, Tirole shares his insights on a broad array of questions affecting our everyday lives and the future of our society, including global warming, unemployment, the post-2008 global financial order, the euro crisis, the digital revolution, innovation, and the proper balance between the free market and regulation.Providing a rich account of how economics can benefit everyone, Economics for the Common Good sets a new agenda for the role of economics in society.
Frontmatter -- CONTENTS -- ACKNOWLEDGMENTS -- INTRODUCTION: WHATEVER HAPPENED TO THE COMMON GOOD? -- PART I. ECONOMICS AND SOCIETY -- ONE. Do You Like Economics? -- TWO. The Moral Limits of the Market -- PART II. THE ECONOMIST'S PROFESSION -- THREE. The Economist in Civil Society -- FOUR. The Everyday Life of a Researcher -- FIVE. Economics on the Move -- PART III. AN INSTITUTIONAL FRAMEWORK FOR THE ECONOMY -- SIX. Toward a Modern State -- SEVEN. The Governance and Social Responsibility of Business -- PART IV. THE GREAT MACROECONOMIC CHALLENGES -- EIGHT. The Climate Challenge -- NINE. Labor Market Challenges -- TEN. Europe at the Crossroads -- ELEVEN. What Use Is Finance? -- TWELVE. The Financial Crisis of 2008 -- PART V. THE INDUSTRIAL CHALLENGE -- THIRTEEN. Competition Policy and Industrial Policy -- FOURTEEN. How Digitization Is Changing Everything -- FIFTEEN. Digital Economies: The Challenges for Society -- SIXTEEN. Innovation and Intellectual Property -- SEVENTEEN. Sector Regulation -- EPILOGUE -- NOTES -- INDEX
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 23. Mai 2019)
Keywords: Common good -- Economic aspects; Economic policy; Economics; BUSINESS & ECONOMICS / Economics / Theory